Hip dysplasia in German shepherd dogs in Turkey - Han, M. C.; Durmus, A. S. (Indian Veterinary Journal, 2006)
Malformationof the coxofemoral joint in dogs or canine hip-dysplasia (CHD) is-a major canine health problem Durmus and Han, 2005; Durmus et al., 2006. Wood et al., 2002). CHD is characterized. by impaired development of the hip joint, which affects the puppies of large and giant breed (Alexander, 1992). The aim of this study was to document the incidence of CHD in German shepherd in Turkey.